Dry sliding behaviour of composite friction materials with varying iron and copper content prepared using the spark plasma sintering technique. (1st January 2022) - Jayashree, Priyadarshini; Menapace, Cinzia; Turani, Simone; Straffelini, Giovanni
ABSTRACT: Composite friction materials, with increasing Fe and decreasing Cu content, were produced using the spark plasma sintering technique. The samples were observed to contain a C-layer deposition on their surfaces, which was due to the C transfer from the graphite die. They were subjected to dry sliding tests on a pin-on-disc testing equipment. The friction and wear behaviour were found to be mainly influenced by the characteristics of the surface C-layer. In the specimens containing high Fe content, the surface C-layer was easily shed during sliding, resulting in elevated coefficient of friction and worn sample surfaces covered with smooth, compact, and continuous friction layer. Conversely, for samples containing low Fe and high Cu content, the C-layer was not completely removed during sliding, leading to low CoF and very mild pin wear. The sliding properties of low Fe content samples were improved with a pre-treatment, wherein the C-layer was mechanically removed.